The ghost of catheter's past: An embolized calcified fibrin sheath after port replacement in a pediatric patient - Mitchell R. Ladd; R. Ellen Jones; Ranim Alsaad; Samuel M. Alaish (Elsevier, 2022)
Herein, we present a rare, although important complication of central venous access in pediatric surgery. Upon exchange of a port, this patient was found to have a calcified fibrin sheath that had embolized into the right pulmonary artery system. Initially, this diagnosis was unclear as it was thought to have been a fractured portion of the catheter. Thus, the patient required multiple diagnostic studies, including a cardiac catheterization to make the final diagnosis. Ultimately, she was treated with anticoagulation and did well. This report highlights the imaging findings of this complication, the diagnostic dilemma it creates, the potential significant consequences, as well as one approach of managing patients with an embolized fibrin sheath from a central venous catheter.